PERHITUNGAN CONNECTIVITY RATIO GARUDA INDONESIA DI BANDAR UDARA INTERNASIONAL SOEKARNO-HATTA (CGK) TAHUN 2018 DENGAN MENGGUNAKAN METODE DANESI - Bayu Riyadi Widhiyanto (Universitas Muhammadiyah Tangerang, 2020)
Flight schedule is one of the products of air transportation, and also one of the competition variables among airlines. Soekarno-Hatta International Airport (CGK) in Jakarta is the main hub of Garuda Indonesia, a full-service carrier in Indonesia. Hub performance can be measured by calculating its connectivity ratio. There are several methods to calculate the connectivity ratio, one of them is a method created by Antonio Danesi in 2006. This paper will explain the calculation of Garuda Indonesia connectivity ratio in CGK by using Danesi method and compare the result with other airports.